Eksistensi Atraksi Pariwisata Di Daya Tarik Wisata Toya Devasya Kintamani (Suatu Studi Pustaka) - Ni Made Ayuk Putriani; I Gusti Agung Oka Mahagangga (JURNAL DESTINASI PARIWISATA, 2020)
Toya devasya is tourist attraction located ini Kintamani subdistrict, Bangli regency. Domestic tourist and international tourist very interested with toya devasya, we should give an appreciation due to management, strategy and travel products, toya devasya felt very fast to built its identity, very interesting and give multiple impact to the local community. Toursm activities have very interesting that sustainability must be pursued. Secondary sources show that the management has made a good effort to manage and establish harmony with the local community. This situation must be pursued for the sustainability of tourism development Method of this research is literature study and the data are qualitative and quantitative, the data source is secondary data by using article tourism science, book and the internet source. The results obtained is the toursm activitiy has not had a positive impact to the local community and the management seem like they are not involved the community in making a decisions, policy maker, to get a benefit from toursm activities. Keywords: Exsistence, tourist attraction, Local Community, Toya Devasya